A case of mistaken identity? Laser-scanning the bronze "Claudius" from near Saxmundham. - Russell, Miles; Manley, Harry (Journal of Roman Archaeology, 2013)
The article discusses the use of laser scanners to determine the identity of the person's head depicted in a Roman bronze sculpture at the British Museum in London, England, which is attributed to depicting the Roman Emperor Claudius. The author contends that the identity of the bronze head at the British Museum may be the Roman Emperor Nero, rather than Emperor Claudius.